Republic of Armenia : Poverty Reduction Strategy Paper: Progress Report. (IMF Staff Country Reports; Country Report ;, 2011)
The main drivers of economic growth in Armenia were the construction and service sectors. The global economic crisis resulted in a substantial change in the structure of the economy. The drastic decline in the volume of foreign financing prejudice the continuation of rapid economic growth in the medium term and point to the need for incentives for exports and diversification, as well as encouraging of high-quality job openings and high levels of productivity. Reforms are needed in the key sectors of agriculture and infrastructure.